Seamless connection : designing safe friendly public realm through creative and innovative landscape design at Maluri, Kuala Lumpur - Ishak, Muhammad Faidhi (2018)
How do we make the public realm more accessible, viable, efficient, safe and friendly at the same time? Every day we often see and hear the issues of inclusivity of the public realm only limited to certain range of users. The current range and manner of satisfying variety of people needs, especially for their daily commuting activities is one of the basic and critical task to do when developing the surrounding environment. Injection element that will eliminate those discomfort environments will be a biggest hope to find justice for all range of users. Public space, is an important element in built environment to enhance the quality of those aspect in public realm. Accessibility relates directly with the built environment and followed by inclusive design that often associated with providing the needs of person with limitation. The aim of this project will be to transform public realm at Maluri, Kuala Lumpur for various range of users using creative and innovative landscape design. Therefore, this project will find the solution and implementing it to achieve a safe and friendly public realm for various range of users. This project emphasizes the importance of enhancing the accessibility aspect in order to create a safe and friendly public space to have the expectation of seamless journey in the built environment. Accessibility may have been provided but restricted and is not designed for all which is essential for various users to participate in social and communal life. Moreover, accessibility is a crucial factor to ensure a conducive living. Designing a safe-friendly environment will help to eliminate the injustice to those who is needed.